Bilateral optic nerve swelling after thyroidectomy followed by a course of radioiodine therapy - E. E. Ioyleva; E. Y. Markova; M. A. Bondarenko (Acta Biomedica Scientifica, 2018)
The most common cancer of the endocrine system is thyroid cancer, representing 1.0-1.5 % all newly diagnosed cases of cancer. According to the cancer society of Russia, the thyroid cancer in children is much rarer than in adults. Thyroid cancer in children and adolescents is characterized by an adverse clinical course and a high risk of developing metastases in the lymph nodes. The main method of treatment for pediatric thyroid cancer is total thyroidectomy with central neck lymph node dissection followed by radioactive iodine therapy. In foreign and domestic literature, complications of the organ of vision, namely, changes of the optic disc, after surgical treatment for thyroid cancer are poorly understood. The risk of transient hypocalcemia and hypothyroidism increases after thyroidectomy. In the literature, there are two reported cases of the optic nerve swelling combined with hypoparathyroidism and hypocalcemia. While hypocalcemia intracranial hypertension and swelling of the optic nerves are often recorded. In this article, the authors present their own clinical observation of a 13-year-old patient after thyroidectomy and radioactive iodine therapy with detailed analysis of the clinical data and study results. According to the survey of the patient, bilateral swelling of the optic disc was revealed, which could occur due to hypothyroid state. Objective: to identify the cause of the development of bilateral optic nerve swelling in a patient after thyroidectomy and treatment course with radioactive iodine.